Uptake and 4-week outcomes of an ‘opt-out’ smoking cessation referral strategy in a London-based lung cancer screening setting - Anthony Edey; Neal Navani; Kitty Chan; Graham Robinson; Janine Zylstra; Paul Robinson; Laura Green; Anand Devaraj; Jane Rowlands; Allan Hackshaw; Carolyn Horst; Arjun Nair; et al. (BMJ Open Respiratory Research)
Introduction Lung cancer screening (LCS) enables the delivery of smoking cessation interventions to a population experiencing long-term tobacco dependence, but the optimal delivery method remains unclear. Here, we report uptake and short-term outcomes of an ‘opt-out’ smoking cessation referral strategy in an LCS cohort.Methods Individuals currently smoking tobacco who attended a face-to-face lung health check in the SUMMIT study (NCT03934866) were offered very brief advice on smoking cessation and where possible, an ‘opt-out’ referral to their local stop smoking service (SSS). Aggregate data on referral outcomes were obtained from each SSS individually.Results 33.7% (n=2090/6203) of individuals currently smoking tobacco consented to a practitioner-made ‘opt-out’ smoking cessation referral. 42.7% (n=893/2090) of these individuals resided in boroughs where SSS were not present or required self-referral. Males (adjusted OR (aOR) 1.16), younger individuals (55–59: aOR 1.70, 60–64: aOR 1.71 and 65–69: aOR 1.78) and those of ethnic minority backgrounds (Asian: aOR 1.31, Black: aOR 1.71 and Mixed: aOR 1.72) were more likely to consent, while individuals from the most deprived socioeconomic quintile were less likely to do so (aOR 0.65).High level of motivation to quit within a defined time frame (aOR 1.92), previous quit attempts in the past 12 months (1–4: aOR 1.65 and ≥5: aOR 1.54) and time to first cigarette of ≤60 min (<5: aOR 2.07, 6–30: aOR 1.55 and 31–60: aOR 1.56) were measures of tobacco dependence associated with a higher likelihood of providing consent.Outcomes were available for 742 referrals. An appointment with the service was accepted by 47.3% (n=351/742) of individuals, following which 65.5% (n=230/351) set a quit date. The 4-week quit rate among those setting a quit date and all individuals referred was 57.4% (n=132/230) and 17.8% (n=132/742), respectively.Conclusion A proactive, ‘opt-out’ smoking cessation referral strategy for individuals currently smoking tobacco who interact with an LCS programme may be beneficial.